2010
DOI: 10.1007/s11033-010-0596-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene polymorphisms in prolactin and its receptor with breast cancer risk in Taiwanese women

Abstract: Given the essential role of prolactin (PRL) and its receptor (PRLR) in breast tumorigenesis, we investigated whether single nucleotide polymorphisms (SNPs) in the PRL and PRLR genes were associated with breast cancer in Taiwanese women. A total of 160 breast cancer patients and 336 unrelated control Taiwanese women were enrolled in this study. Three SNPs (rs1341238, rs2244502 and rs3756824) in the PRL gene and one SNP (rs10941235) in the PRLR gene were genotyped using allele-specific polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Activation of PRLR-JAK2-STAT3/5 signaling has been implicated in the up-regulation of steroid hormone receptor expression and malignant progression of breast cancer (Chan et al, 2014; Fiorillo et al, 2013). There is also support for an association between PRLR allelic variations and breast cancer risk (Bogorad et al, 2008; Lee et al, 2007; Mong et al, 2011; Vaclavicek et al, 2006). In lobular neoplasia, amplification of PRLR may also be important for pathogenesis and progression (Tran-Thanh et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Activation of PRLR-JAK2-STAT3/5 signaling has been implicated in the up-regulation of steroid hormone receptor expression and malignant progression of breast cancer (Chan et al, 2014; Fiorillo et al, 2013). There is also support for an association between PRLR allelic variations and breast cancer risk (Bogorad et al, 2008; Lee et al, 2007; Mong et al, 2011; Vaclavicek et al, 2006). In lobular neoplasia, amplification of PRLR may also be important for pathogenesis and progression (Tran-Thanh et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…A recent follow-up study found that elevated circulating PRL ten years prior to diagnosis was associated with risk for metastatic ER+ disease [5]. Second, recent studies have identified polymorphisms in the PRLR and PRL genes associated with breast disease [6-8]. …”
Section: 1 Prolactin and Breast Cancermentioning
confidence: 99%
“…Several genetic polymorphisms in PRL/PRLR have been studied in various ethnic population for breast cancer susceptibility and aggressiveness (8)(9)(10). For example, PRL rs3756824 and rs2244502 polymorphisms were associated with different plasma PRL levels in a multiethnic cohort (8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PRL rs3756824 and rs2244502 polymorphisms were associated with different plasma PRL levels in a multiethnic cohort ( 8 ). Furthermore, PRL rs3756824 was correlated with breast cancer metastasis in Taiwanese population ( 9 ). PRLR rs37364 and rs249537 were correlated with breast cancer risk in Polish women ( 11 ).…”
Section: Introductionmentioning
confidence: 99%